Management of human resources in professional sports clubs as one of the requirements for the success of sports professionalism in Algeria. - nadir.bouslah (sports creativity, 2025)
Study Summary: In this research, we discussed the role of human resources management in professional sports clubs as one of the requirements for the success of sports professionalism in Algeria, In the light of the application of sports professionalism for a short period of time, the professional sports clubs must follow the modern methods of management and administration, And give great importance to the management of human resources and knowledge the principal role of the leaders for developing the intellectual and creative capabilities of staff and administrators in order to achieve the objectives., we used In this study the descriptive method on a sample of 30 members of the Board of Directors of professional sports clubs, The clubs were chosen randomly, and we used a questionnaire as a tool for collecting information. The main results of the study were that the management of human resources in professional sports clubs is considered one of the requirements for the success of sports professionalism in Algeria. The most important suggestions are: assign specialists to establish a unit or a committee for the management of human resources in professional sports